Modification of the band gaps and optical properties of single-walled carbon nanotubes - Wiltshire, J; Li, L; Khlobystov, A; Glerup, M; Bernier, P; Nicholas, R (2005)
We report a study of the effects of various sample purification and modification techniques on the band gaps and optical properties of bulk single walled carbon nanotubes (SWNTs). These include a variety of thermal and chemical oxidation treatments and a study of nitrogen and boron doping.